Islam and gender: statutory rape cases among Malays in Kuala Lumpur, Malaysia - Mohd Noor, Noor Azlan; Mohamad Yunus, Mohamad Ismail; Ahmad Tajudin, Bazlin Darina (2011)
In Muslim societies, girls and boys are expected to behave in accordance with social, cultural and most importantly, Islamic teachings. In Islam, interactions between the sexes are permitted within certain limits specified by the Qur’an and Sunnah. Sadly to say, despite all of this, statistics have shown that the number of rape cases involving Muslims, i.e., the Malays are much higher compared to other ethnic groups, i.e., the non-Muslims. This paper attempts to examine statutory rape among Malay teenagers with reference to Kuala Lumpur, Malaysia. Statutory rape refers to crime committed to a victim by a perpetrator; both are whom below 16 years old. This study was conducted at the Kuala Lumpur Contingent Police Headquarter (IPK, KL) involving 18 statutory rape cases in police reports and statements for the year 2006 to 2009. Several important findings are discovered throughout the study, of which there are certain factors that contribute to statutory rape. The factors include, among others, coupling at a young age, lepak (loafing) and poor parenting. It is pertinent for the authority to identify these factors and at the same time, provide effective mechanisms to curb these statutory rape cases from becoming rampant among the Muslims in Malaysia, particularly among teenagers. Finally, this paper will also provide guiding principles to create cognizance in regards to parents’ liberal idea on the interaction between males and females that encourage teenagers eventually to have sex at a very young age. Keywords: Islamic teachings, Malays, teenagers, interactions, statutory rape